Improving livestock water productivity - Wright, Iain A. (2013)
Demand for livestock products is increasing rapidly in the developing world as a consequence of population growth, rising incomes, urbanization, and changes in dietary preferences. The livestock sector now accounts for about 40% of agricultural GDP in developing countries, although the investment in the sector falls far short of its economic importance. While this increasing demand presents opportunities, especially for small -hold farmers, to supply livestock products, it also puts pressure on the natural resource base, including pressure on water resources . Livestock water productivity (LWP) —a measure of the efficiency with which water is used to produce economic benefit from livestock—varies widely among systems, but data on different systems, particularly in developing countries, is scarce. Since water for growing feed is the major water requirement in livestock systems, any measures to improve efficiency of water use for producing feed will have a major effect on LWP. Improving animal productivity also increases LWP, as a lower proportion of the total feed intake (and hence water requirement) is used for maintaining the animal. National governments and international agencies should increase the proportion of agricultural research and development budgets spent on livestock to 20%. This should include providing better estimates of the use of water and LWP for different livestock systems. Major improvement in LWP could be achieved if investments were made in improving livestock productivity through research, development ,and exte nsion. Design of irrigation systems needs to include the water demand for production of feed for livestock as well as crops.